《二刻拍案惊奇》中的妇女形象 = A portrayal of women in amazing tales : second series (Er Ke Pai An Jing Qi) - 黎秋仪 Lai, Qiuyi (2009)
封建社会发展到明代，中国妇女对“贞节” 的崇尚达到了登峰造极的地步，究其原因，主要有两点；一是封建政府长期以来对妇女实施的严厉封建教育；一是明政府推行的一系列旌表制度，促使明朝妇女把“节烈”作为丧夫后的最佳选择，自愿过悲惨的寡居生活。但是到了明代中后期，商品经济的发展促使社会价值观和风俗发生很大变化，妇女反礼教思想也因此盛行。因此《二刻拍案惊奇》作为反应市井生活为主要内容的白话小说，从考察当中的众多妇女形象可以发现《二刻》的女性贞节观有其突破性的。在作品中，贞节已不是女性婚姻生活的最高准则。作品提倡贞节与情爱的统一，主张以追求幸福突破贞节的枷锁。对于贞节观念的受害者，作品既有同情也有赞颂，却缺少理性的批评和反思，贞节仍然作为一种女性的人生价值和社会伦理原则被尊崇。《二刻》的贞节观念更大程度地停留在封建教化上，与男女平等的现代观念还有一定的距离。There are mainly two causes for the Chinese women to uphold their “Chastity” till the maximum level that the past dynasties have ever reached when the feudal society has reached its peak as it came to Ming dynasty. Firstly, it was because of the government’s harsh implementation of feudal education on the women and secondly it was because of the series of testimonials conferred by the emperor to the women who died to protect their chastity, therefore causing the women in Ming dynasty to value their chastity as it seems to be an honorable act and thus they chose to stay widowed all their lives. However, in the late Ming dynasty, there were great developments in economy causing a great change in society values and traditions. Therefore, in response to the change in societal views, the counter-Confucianism thoughts were also in vogue. Thus, “Amazing Tales – Series 2” (Er Ke Pai An Jing Qi) being a collection of short stories of lives of the peasants, we would discover that there is a breakthrough in the view of women’s chastity from analyzing the images of women in the stories. In the stories, “chastity” is no longer the highest regard in women’s marriage and “Amazing Tales – Series 2” advocate women pursuing their own wants, aiming to break free from the traditional thinking. The author shows his sympathy for those who suffered under the feudalism and sang praises of those who dared to take a step forward in breaking free. However, the author lacks the rational criticism and reflection on this matter as chastity still remained important as one of the feminine’s social ethics. Thus, the view of chastity in “Amazing Tales – Series 2” remained stagnant at feudalism, being a distance away from the present view of man and women being equal in status.